Parliament as theatre: Francis Wheatley's The Irish House of Commons revisited - Cullen, Fintan (Irish Academic Press, 2016)
Examination of a painting produced in Dublin in 1780 of the interior of the Irish House of Commons. Explores the format of the painting and its failure as a large scale work of contemporary history. Concludes that contents of picture is a political and social illusion.